Verification and evaluation of computer and communication systems : 11th International Conference, VECoS 2017, Montreal, QC, Canada, August 24-25, 2017, Proceedings /: 11th International Conference, VECoS 2017, Montreal, QC, Canada, August 24-25, 2017, Proceedings. (2017) - Unknown
No abstract available